Motivational Elements in Malay and Arabic Proverbs: A Rhetorical and Psychological Analysis - Wan Azura Wan Ahmad; Ahmad Fazullah Mohd Zainal Abidin; Yuslina Mohamed; Mohamed Haji Ibrahim; Aishah Isahak (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia